Sexuality education through short stories - Gunalingam Krishnan,; Zalina Mohd Lazim,; Noraini Md Yusof, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Issues pertaining to sexual misbehaviour among adolescents have continued to make headlines in the Malaysian media. In response to this, the Malaysian government decided to introduce sex education in the schools beginning January 2011. However, with resounding pessimistic views from conservatives that the introduction of sex education in schools could be misconstrued by students as an initiation to sexual activities, careful consideration needs to be given to how the topic is introduced and handled and the materials utilised in the teaching of sexuality education. In the West, literature has been successfully utilised in various fields of works in a bid to alter perceptions and awareness of individuals. This paper seeks to discuss the feasibility of using short stories to enhance students’ level of awareness on issues pertaining to sexuality. A research was conducted to study the feasibility of teaching sexuality education through selected short stories that deal with issues on abortion, pre-marital sex, gender roles, and gender equality to a group of students in a Malaysian classroom. The first section provides a literature review and argues the rationale for the selection of short stories to teach sexuality education. Data from a pilot study will provide indications as to the feasibility of using short stories to teach sexuality education. This paper concludes by deliberating on the feasibility of using short stories as an alternative way to enhance students’ knowledge and awareness on issues pertaining to sexuality.